Peran Artificial Intelligence (AI) dalam Manajemen Arsip dan Dokumen - Yulianto, Erwin; Murdianto, Teguh; Al-Amin, Al-Amin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study examines the role of Artificial Intelligence (AI) in records and document management through an in-depth literature review. It was found that AI has significant potential to enhance the efficiency and accuracy of archival data management. With AI's ability to automate indexing, classification, and data processing processes, researchers noted a considerable reduction in human errors. Additionally, AI plays a crucial role in the security and accessibility of documents by providing robust data encryption and stringent access filtering. This technology also simplifies document searches, enabling users to find information quickly and efficiently. In conclusion, integrating AI into records and document management brings significant technical and operational benefits. This literature review underscores that AI can improve the performance and reliability of information management systems. With these capabilities, AI is expected to pave the way for more effective, efficient, and secure archival management. The study provides insights that AI is not just an advanced solution but also a critical tool for the future of records and document management in various organizations.